2021
DOI: 10.1002/cnr2.1406
|View full text |Cite
|
Sign up to set email alerts
|

Bladder and upper urinary tract cancers as first and second primary cancers

Abstract: Background: Previous population-based studies on second primary cancers (SPCs) in urothelial cancers have focused on known risk factors in bladder cancer patients without data on other urothelial sites of the renal pelvis or ureter.Aims: To estimate sex-specific risks for any SPCs after urothelial cancers, and in reverse order, for urothelial cancers as SPCs after any cancer. Such two-way analysis may help interpret the results. Methods:We employed standardized incidence ratios (SIRs) to estimate bidirectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“… . Stomach: 751 Pancreas: 137 Ovary: 34 1.37 (1.28–1.47) 1.21 (1.02–1.43) 1.83 (1.27–2.56) 7 Ye et al [ 35 ] Retrospective cohort study Australia; Tasmanian Cancer Registry Men and women with a diagnosis of cancer > 2 months; aged > 15 years 1980–2009; 6.9 years (mean) 51,802 28,242 (54.5%) 23,560 (45.5%) 66.2 (median) Lung: 121 Skin: 80 Prostate: 182 1.13 (0.80–1.58) 1.88 (1.38–2.55) 1.15 (0.90–1.48) 8 Zheng et al [ 37 ] Retrospective cohort study Sweden; Swedish Cancer Registry Men and women with a diagnosis of bladder or upper urinary tract cancer 1990–2015; average follow-up unknown 49,584 36,614 (74%) 12,970 (26.0%) 73 (median) Urinary bladder: 521 Kidney: 22 1.11 (1.02 –1.21) 1.32 (0.83–1.54) 8 Zheng et al [ 38 ] Retrospective cohort study Sweden; Swedish Cancer Registry Men and women with a diagnosis of hepatobiliary cancer 1990–2015; 36 months (median) 19,995 10,102 (64.9%) 9893 (49.5%) 72 (median) Gallbladder: 44 Bile duct: 61 0.85 (0.61–1.14) 1.20 (0.92–1.54) 8 *Newcastle–Ottawa Scale ratings ≥ 6 were considered high quality …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… . Stomach: 751 Pancreas: 137 Ovary: 34 1.37 (1.28–1.47) 1.21 (1.02–1.43) 1.83 (1.27–2.56) 7 Ye et al [ 35 ] Retrospective cohort study Australia; Tasmanian Cancer Registry Men and women with a diagnosis of cancer > 2 months; aged > 15 years 1980–2009; 6.9 years (mean) 51,802 28,242 (54.5%) 23,560 (45.5%) 66.2 (median) Lung: 121 Skin: 80 Prostate: 182 1.13 (0.80–1.58) 1.88 (1.38–2.55) 1.15 (0.90–1.48) 8 Zheng et al [ 37 ] Retrospective cohort study Sweden; Swedish Cancer Registry Men and women with a diagnosis of bladder or upper urinary tract cancer 1990–2015; average follow-up unknown 49,584 36,614 (74%) 12,970 (26.0%) 73 (median) Urinary bladder: 521 Kidney: 22 1.11 (1.02 –1.21) 1.32 (0.83–1.54) 8 Zheng et al [ 38 ] Retrospective cohort study Sweden; Swedish Cancer Registry Men and women with a diagnosis of hepatobiliary cancer 1990–2015; 36 months (median) 19,995 10,102 (64.9%) 9893 (49.5%) 72 (median) Gallbladder: 44 Bile duct: 61 0.85 (0.61–1.14) 1.20 (0.92–1.54) 8 *Newcastle–Ottawa Scale ratings ≥ 6 were considered high quality …”
Section: Resultsmentioning
confidence: 99%
“…The risk of several second primary cancers was significantly higher in patients with CRC compared with the general population’s risk of developing respective primary cancers. The risk of subsequent malignancies was greatest in the small intestine (pooled SIR = 4.26 (95% CI = 2.58–7.01; p < 0.0001)) from four studies [ 18 , 21 , 32 , 33 ]; followed by the female genitals (1.88 (1.07–3.31; p = 0.03)) from three studies [ 16 , 32 , 34 ]; kidney (1.50 (1.19–1.89; p = 0.0007)) from seven studies [ 16 , 18 , 21 , 32 – 34 , 37 ]; thyroid (1.40 (1.28–1.53; p < 0.0001)) from three studies [ 33 , 34 , 36 ]; skin (melanoma) (1.28 (1.01–1.62; p = 0.04)) from eight studies [ 16 , 18 , 21 , 30 , 32 35 ]; stomach 1.22 ((1.07–1.39; p = 0.003)) from seven studies [ 16 , 18 , 21 , 27 , 32 – 34 ]; urinary bladder (1.19 (1.06–1.33; p < 0.0001)) from seven studies [ 16 , 18 , 21 , 32 – 34 , 37 ]; and lung, bronchi, and mediastinum (1.16 (1.01–1.32; p = 0.03)) from seven studies [ 16 , 18 , 21 , 32 35 ]; Fig. 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a kind of urothelial cancer, bladder cancer is the utmost prevalent malignancy comprising the urinary system and the ninth most common malignancy worldwide [ 3 ]. Histologically, bladder cancer can categorize into three main kinds: metastatic bladder cancer, muscle invasive and non-muscle invasive [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of new occurrences and deaths of malignant neoplasms of the urinary tract (MNUT) has increased year by year, with figures for bladder and kidney neoplasms reaching 1.005 million and 392,000, respectively (1). Benefiting from the great advances in diagnostic techniques and treatment methods for MNUT, the survival rate of patients is gradually improving (2,3). Studies have shown that second primary malignancy (SPM) is a serious and potentially fatal long-term complication of cancer patients, which places a heavier burden on the survival of patients with MNUT (4).…”
Section: Introductionmentioning
confidence: 99%